СИСТЕМА ИЗОБРАЗИТЕЛЬНО-ВЫРАЗИТЕЛЬНЫХ СРЕДСТВ, ИСПОЛЬЗОВАННЫХ М.А.БУЛГАКОВЫМ В СОЗДАНИИ ОБРАЗА ВОЛАНДА - Оразымбетова, Ш.А. (SCIENCE and SOCIETY, 2018)
The article is devoted to the interpretation of the system of expressive means used by M.A. Bulgakov in the work "The Master and Margarita" in the creation of the image of Woland.